2014
DOI: 10.1002/asia.201402657
|View full text |Cite
|
Sign up to set email alerts
|

Residual Metal Impurity Aids Facile In Situ Electrochemical Surface Derivatization of Single‐Walled Carbon Nanotubes

Abstract: Residual metal impurities were exploited as reactants in the functionalization of the surface of single-walled carbon nanotubes (SWCNT) with nickel hexacyanoferrate (NiHCF) by simple electrochemical cycling in ferricyanide solutions. This facile in situ electrochemical modification process provides intimate contact between NiHCF and SWCNTs that improves the stability of the redox property and reactivity of NiHCF. The characteristic redox behavior of NiHCF on SWCNT surfaces can be used as an electrochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…Our group has also reported that the presence of residual metal impurities in SWCNTs act as an active site for selective deposition of ZnHCF on SWCNT modified GCE , which shows enhanced pseudo‐capacitance property. In addition, the same residual impurity in SWCNT leads in‐situ formation of NiHCF and Ni(OH) 2 /NiOOH composite on SWCNT when simple electrochemical cycling in alkaline solution and shows the high pseudo‐capacitance as well as enzyme‐less glucose oxidation .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our group has also reported that the presence of residual metal impurities in SWCNTs act as an active site for selective deposition of ZnHCF on SWCNT modified GCE , which shows enhanced pseudo‐capacitance property. In addition, the same residual impurity in SWCNT leads in‐situ formation of NiHCF and Ni(OH) 2 /NiOOH composite on SWCNT when simple electrochemical cycling in alkaline solution and shows the high pseudo‐capacitance as well as enzyme‐less glucose oxidation .…”
Section: Introductionsupporting
confidence: 76%
“…The detailed characterization of SWCNT using ICP‐MS and TEM has been discussed in our earlier reports . As received SWCNTs have several metal impurities such as Ni (8.7 %), Fe (4.5 %) and Zn (7 %) based on ICP‐MS analysis and the morphology of these metal impurities in SWCNTs were further confirmed by TEM analysis.…”
Section: Resultsmentioning
confidence: 92%